COMPARATIVE LITERATURE AND ITS FEATURES - Fatkullaeva Viktoria Sayfullaevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the issues of comparative literature, national literary events in the context of the socio-cultural development of nations, the relationship with cultural and literary views between them.